E-Commerce and Web Marketing as an Answer to the Global Market. Methods in Web Marketing - Foglio, Antonio; Stanevičius, Vaidotas (Ekonomika, 2002)
In this paper the authors present the process of web marketing as a specific subject and as an integration of the traditional marketing. The conclusion is that e-commerce and web marketing are a pragmatic and modern answer to the globalization; presenting the process of web marketing the authors outline the necessary methods in teaching web marketing and the new professionalism required.